Influence of the use of inoculum in the estimation of methane gas in organic waste in the landfill of the municipalities of agreste alagoano (Research, Society and Development, 2021)
One way to take advantage of the energy available in the waste, stabilize and reduce the volume of the organic fraction to be sent to landfills is through anaerobic digesters. The research aims to evaluate the production of methane gas from the anaerobic digestion of the organic fraction of the MSW of the Sanitary Landfill of Agreste Alagoano, through tests of Methane Biochemical Potential, with and without the use of inoculum. For this purpose, six 1L discontinuous hydraulic flow reactors were used, with a reaction volume of 400mL, three reactors with inoculum and three others with the organic fraction without inoculum. The greatest potential was observed in the reactors with inoculum, of 7926.31 mL, with peak production on the 10th day of operation, and also obtained the highest methane production rate of 1491.16 mL.h-1. The reactors without inoculum had lower potential and methane production rate, 1020.42mL and 28.40mL.h-1, their maximum production occurred on the 30th day of operation. With this, it is verified the importance of the use of inoculum for a greater potential generation of methane gas in the anaerobic digestion of MSW of the landfill under study, which can be used as an alternative source of energy for domestic and industrial purposes.